On the role of saturation in modeling ionic transport in the electrolyte of (Lithium ion) batteries - Salvadori, A.; Grazioli, D.; Magri, M.; Geers, M.G.D.; Danilov, D.; Notten, P.H.L. (Journal of power sources, 2015)
Recent computational simulations of ionic conductivity across the electrolyte of commercial batteries by Salvadori et al. (2015) have shown that the concentration of ions exceeds half the saturation limit near the electrodes. This observation, which is in agreement with other approaches by Danilov and Notten (2008), implies that the widespread assumption of infinite dilution far from saturation is questionable. The present contribution is therefore devoted to investigate the role of saturation in modeling ionic transport in the electrolyte of Li-ion batteries. An important result is found, that saturation has no effect on the diffusivity, whereby the condition of electroneutrality is well approximated in the solution. However saturation affects the electric potential up to 40% near the electrodes for all charge rates. •We developed a novel approach in modeling ionic transport in the electrolyte.•We considered fundamental laws with no recourse to electroneutrality equation.•Constitutive theory, weak forms, simulations are framed in a rigorous PDEs setting.•Saturation in the electrolyte is considered and its impact analyzed.•Results show that saturation might significantly impact on the electric potential.